TRANSFORMASI PENDIDIKAN ISLAM MELAYU DI SUMATERA BARAT DARI SURAU KE MADRASAH MODERN PADA AWAL ABAD KE-20 - Ismarani Junia Putri; Sandrina Ramadhani; Izzatuzzahroh; Maryamah; Zulhijra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the transformation of Malay Islamic education from the traditional surau system to modern madrasah institutions in the early twentieth century in West Sumatra. The research employs a qualitative approach using the Systematic Literature Review (SLR) method to synthesize relevant scholarly findings on the institutional development of Islamic education within Minangkabau society. Data were collected through systematic identification, selection, and critical evaluation of academic literature addressing the surau educational system, the emergence of modern madrasahs, and the modernization of Islamic education. The findings indicate that educational transformation emerged as a response to social and intellectual changes and the growing need for a more structured educational system. Modern madrasahs introduced organized curricula, formal institutional management, and the integration of religious and general sciences while preserving traditional Islamic values. This transformation reflects the adaptive capacity of Malay Islamic education in responding to modernity while maintaining its religious foundations. Therefore, the shift from surau to modern madrasah represents a significant milestone in the historical development of Islamic education in Indonesia.